Reading for Information at Secondary School Level - Saravia, Graciela; Carlsen, Elena; Briones, Susana; Moreno, Laura; Fernandez, Susana (The ESPecialist, 2012)
The purpose of this paper is to report on the results obtained in a study carried out in a fifth year of a secondary school to prove the advantage of limiting the objectives of English courses to Reading Comprehension in the last year of public secondary school.The procedures used to collect the data were questionnaires, tests, the school teacher’s report and the research team’s report.The results of this study showed that the emphasis on reading comprehension is advisable due to the English teaching situation in the North of Argentina.